The Design of Digital of information System For Shipbuilding Proccess : Current Condition of Medium Shipyard (Naval Architecture Departement, Hasanuddin University, 2022)
In the era of the industrial revolution 4.0, information technology is developing very rapidly so that it is now easier to design an information system that can facilitate aspects of work. The ship production process in a shipyard involves complex information. It's the necessary information to keep the shipbuilding project progress with the Plan. Unclear information at least one of the stages in the ship production process will delay project completion and affect costs. Manually distributing important information about the shipbuilding process to related departments takes time. Therefore, it directly affects the duration of the project. A digital information system for the shipbuilding process is needed to overcome these problems. Therefore, it is necessary to develop an integrated information system that functions to facilitate the flow of information between divisions related to the ship production process in the form of digitization. Based on this, there has been no digitalization of information system integration related to production materials in the design division (Engineering), purchasing division, material warehouse division and production division. Therefore, before the digital information system can be developed further, it is necessary to identify and formulate the flow of information between departments. Therefore, this study aims to identify and formulate information and flows to the four divisions in the ship production process .